Let it snow : [large type] a novel - Thayer, Nancy, 1943- (Center Point Large Print, 2019)
Christina Antonioni is preparing for the holidays at her Nantucket toyshop, unpacking last-minute shipments and decorating for her loyal Christmas shoppers. But when her Scrooge of a landlord, Oscar Bittlesman, raises her rent, it seems nearly impossible for Christina to continue business on the wharf. Even so, Christina firmly believes there may be a warm heart underneath Oscar's steely exterior. When she bonds with Wink, his sweet, young granddaughter who frequents the shop, it becomes clear that perhaps he isn't so cold after all. And with the help of Wink's uncle, who happens to be a charming (and extremely wealthy) bachelor, this may be the best Christmas any of them could have ever imagined.